Pleural malignant mesothelioma with metastatic deposition in the tongue. Issue 6 (15th June 2021) - Steward, Matthew; Pearce, Catharine; Powari, Manish; Bakere, Hugh
Abstract : A 70-year-old man with epithelioid malignant pleural mesothelioma was referred to the maxillofacial surgery department with a painful lesion on the lateral border of his tongue which interfered with swallowing. Physical examination demonstrated a 3 cm firm, non-ulcerated mass on the left lateral tongue, histologically shown to be metastatic epithelioid mesothelioma. MRI of the neck and CT scan of the thorax, abdomen and pelvis scans also demonstrated progressive local and metastatic disease. The patient was not felt to be fit for further treatment. More than 90% of oral cavity cancers are squamous cell carcinoma. All reported cases of metastasis of malignant mesothelioma to the tongue have been of the epithelioid subtype with 10 cases reported in the literature to date. Diagnosis is important as tongue lesions can significantly impact on quality of life and synchronous tongue primaries should be ruled out. Tongue lesions may herald metastases to other extrapleural locations.